2023
DOI: 10.1111/den.14500
|View full text |Cite
|
Sign up to set email alerts
|

Polyp characterization using deep learning and a publicly accessible polyp video database

Abstract: Objectives: Convolutional neural networks (CNN) for computer-aided diagnosis of polyps are often trained using high-quality still images in a single chromoendoscopy imaging modality with sessile serrated lesions (SSLs) often excluded. This study developed a CNN from videos to classify polyps as adenomatous or nonadenomatous using standard narrow-band imaging (NBI) and NBI-near focus (NBI-NF) and created a publicly accessible polyp video database. Methods:We trained a CNN with 16,832 high and moderate quality f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…The results showed that referring to NBI-CAD results significantly improved the diagnostic sensitivity, NPV, and accuracy, regardless of the endoscopist's expertise. Several CADx systems for colorectal polyps have been used to date, [17][18][19][20][21] and their clinical diagnostic performances have been reported. 9,[22][23][24] Similar to our precedent study, some studies reported that PIVI-1 9,23 and PIVI-2 9,22 thresholds could be achieved, which could facilitate the widespread adoption of CADx in clinical practice.…”
Section: Discussionmentioning
confidence: 99%
“…The results showed that referring to NBI-CAD results significantly improved the diagnostic sensitivity, NPV, and accuracy, regardless of the endoscopist's expertise. Several CADx systems for colorectal polyps have been used to date, [17][18][19][20][21] and their clinical diagnostic performances have been reported. 9,[22][23][24] Similar to our precedent study, some studies reported that PIVI-1 9,23 and PIVI-2 9,22 thresholds could be achieved, which could facilitate the widespread adoption of CADx in clinical practice.…”
Section: Discussionmentioning
confidence: 99%
“…Hybrid AI systems may be especially relevant in contexts such as colonoscopies by nonexpert endoscopists with low ADR or in fecal occult blood test-based screening programs where the prevalence of neoplastic lesions is higher. However, there are concerns regarding the usefulness of certain endoscopic technological innovations in CRC screening programs since they do not always increase the ADR when patients undergo high-quality colonoscopy by endoscopists with a high ADR [ 51 , 52 , 59 , 61 , 62 , 63 , 64 ].…”
Section: Computer-aided Polyp Detection (Cade)mentioning
confidence: 99%
“…Artificial intelligence (AI) was introduced in clinical practice several years ago, with the main focus being polyp detection 12 13 ; however, AI-based diagnosis has been further explored for polyp characterization 14 and other gastroenterological diseases, such as eosinophilic esophagitis 15 and Crohn's disease 12 . AI has the potential to solve the issue of polyp sizing, and several AI-based concepts have recently been described 16 17 18 .…”
Section: Introductionmentioning
confidence: 99%